2012
DOI: 10.1002/jor.22245
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the position of the acetabulum in a ganz periacetabular osteotomy by finite element analysis

Abstract: Periacetabular osteotomy (PAO) is a surgical procedure to correct acetabular orientation in developmental dysplasia of the hip (DDH). It changes the position of the acetabulum to increase femoral head coverage and distribute the contact pressure over the cartilage surface. The success of PAO depends significantly on the surgeon's experience. Using computed tomography data from patients with DDH, we developed a 3D finite element (FE) model to investigate the optimal position of the acetabulum following PAO. A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 37 publications
10
89
0
1
Order By: Relevance
“…Finite element analysis has shown that reconstructive procedures such as the Bernese periacetabular osteotomy (PAO) can increase joint contact area and decrease joint contact pressures [6,36] but cannot reach predicted normal values, probably because of the irregular shape of dysplastic hips [20,74]. Medium-term results (5.5 years to 15 years) after PAO show a rate of conversion to THA between 7% and 15% [19,36,43,68].…”
Section: Discussionmentioning
confidence: 99%
“…Finite element analysis has shown that reconstructive procedures such as the Bernese periacetabular osteotomy (PAO) can increase joint contact area and decrease joint contact pressures [6,36] but cannot reach predicted normal values, probably because of the irregular shape of dysplastic hips [20,74]. Medium-term results (5.5 years to 15 years) after PAO show a rate of conversion to THA between 7% and 15% [19,36,43,68].…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling has been extensively applied to the lower extremity to evaluate in vivo joint mechanics [4][5][6][7][8][9][10][11]18]. In the wrist, studies have evaluated in vivo joint mechanics during functional activities [12,14,16,17] and have also simulated the effects of some carpal fractures and limited fusions [13,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…The common techniques include image-based FEM [4][5][6][7][8][9][10][11][12][13], rigid body spring modeling/discrete element analysis (RBSM) [14][15][16], or SCM [17][18][19]. The models are either displacement driven or force driven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, variability in the extent of acetabular cartilage development has received increasing research interest and has been investigated as a major cause [6]. Steppacher et al [7] found that patients with acetabular dysplasia had a clearly decreased lunate surface size, decreased outer acetabular rim, and increased acetabular fossa.…”
Section: Introductionmentioning
confidence: 99%